The role of exercise-related FNDC5/irisin in depression - Liu, Yaqi; Fu, Xiying; Zhao, Xing; Cui, Ranji; Yang, Wei (Frontiers in Pharmacology, 2024)
The complexity of depression presents a significant challenge to traditional treatment methods, such as medication and psychotherapy. Recent studies have shown that exercise can effectively reduce depressive symptoms, offering a new alternative for treating depression. However, some depressed patients are unable to engage in regular physical activity due to age, physical limitations, and other factors. Therefore, pharmacological agents that mimic the effects of exercise become a potential treatment option. A newly discovered myokine, irisin, which is produced during exercise via cleavage of its precursor protein fibronectin type III domain-containing protein 5 (FNDC5), plays a key role in regulating energy metabolism, promoting adipose tissue browning, and improving insulin resistance. Importantly, FNDC5 can promote neural stem cell differentiation, enhance neuroplasticity, and improve mood and cognitive function. This review systematically reviews the mechanisms of action of exercise in the treatment of depression, outlines the physiology of exercise-related irisin, and explores possible mechanisms of irisin's antidepressant effects. The aim of this review is to encourage future research and clinical applications of irisin in the prevention and treatment of depression.